2001
DOI: 10.1097/00005537-200101000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Argon Plasma Surgery for the Inferior Turbinate of Patients With Perennial Nasal Allergy

Abstract: This is the first report on the clinical effects of turbinate surgery for nasal allergy using APC. APC was useful fer turbinate surgery of nasal allergy, especially for nasal stuffiness and congestion of the turbinate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…This produces tissue desiccation but preserves the mucosa and has shown promising 1-year results. 533 Radiofrequency ablation (RFVTR), a relatively new technique conducted under local anesthesia, creates ionic agitation in the tissue, inducing submucosal necrosis and fibrosis and reduced blood flow to the turbinate. Resultant wound contraction causes volume reduction of the inferior turbinate without damage to the overlying mucosa and preserves mucociliary clearance.…”
mentioning
confidence: 99%
“…This produces tissue desiccation but preserves the mucosa and has shown promising 1-year results. 533 Radiofrequency ablation (RFVTR), a relatively new technique conducted under local anesthesia, creates ionic agitation in the tissue, inducing submucosal necrosis and fibrosis and reduced blood flow to the turbinate. Resultant wound contraction causes volume reduction of the inferior turbinate without damage to the overlying mucosa and preserves mucociliary clearance.…”
mentioning
confidence: 99%
“…Concerning the effects of APC on the physiology of the nasal mucosa, regeneration of epithelial cells occurred within 3 months and mucociliary clearance did not change significantly in APC-treated areas [29].…”
Section: Discussionmentioning
confidence: 90%
“…Fukazawa et al 4 investigated histological changes in the mucosa of inferior tur· binate after surgery, and they observed that the mucosal surface was covered with non-ciliated cuboidal epithelium at postoperative month 3, showing fibrosis of the lamina propria mucosae and a decrease in nasal glands. By contrast, it was reported that the mucosal epithelium returned to the same ciliated epithelium as that seen before surgery at 3 months after surgery, and no differences were observed between pre-and post-operative results of mucus ciliary function test.…”
Section: Discussionmentioning
confidence: 99%